OXFORDIAN BIOSTRATIGRAPHY AND AMMONITE ASSOCIATIONS FROM WEST SICILY: BIOSTRATIGRAPHIC SUCCESSION OF GENUS GREGORYCERAS AND CORRELATION WITH TETHYAN PERISPHINCTID SCALE (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2004)
Middle to lower upper Oxfordian ammonite successions from northwest Sicily, are mainly composed of groups showing a typical Mediterranean character. These include common representatives of suborder Phylloceratina. Among Ammonitina, the bulk of recorded associations is formed by representatives of Mediterranean subfamilies Passendorferiinae, Euaspidoceratinae and Peltoceratinae, with a minor representation of family Oppeliidae. The studied ammonite associations include over two hundred specimens, from which, a whole of one hundred and fifty have been identified and described. They have been collected from three sections located on the southern side of Mount Erice, southwest from the town of Erice (Trapani province). Taphonomic features displayed by the recorded ammonites indicate, on one hand, sedimentation conditions on an open hemipelagic platform under low turbulence conditions and low sedimentation rate values. On the other hand, Perisphinctid (Passendorferiinae) and Aspidoceratidae assemblages appear dominated by juvenile or pre-adult specimens, indicating palaeobiological entities probably colonizing the area and spreading to epicontinental areas farther North from the southern slope of Tethys. From the biostratigraphic point of view, stratigraphic succession of representatives of genus Gregoryceras has allowed recognising a biostratigraphic succession in the Mediterranean Province, which can closely correlate with the one established with representatives of Passendorferia and Perisphinctes for the Submediterranean Province.